2018
DOI: 10.1038/s41598-018-34370-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relations between 3-year Changes in Physical Fitness and Academic Performance in Nationally Representative Sample of Junior High School Students

Abstract: The objective of the current study was to examine the relationship between different components of physical fitness across 3 years of junior high school with academic performance assessed at the end of the period. Two nationwide representative datasets were used. The first was the physical fitness profile assessed at the beginning of each of the three school years. The second contained the scores on a standardized test administered at the end of the third year. All data were standardized by calculating percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…In our study, although an interaction effect of baseline BMI and BMI changes on changes in academic performance over 2 years was noted, changes in BMI had no main effect on changes in academic performance over 2 years. These results could partly explain the weak or null association of BMI changes with academic performance in Asian children as previously reported 6,24 . Furthermore, a previous crosssectional study demonstrated an inverted U-shape relationship between BMI and academic performance in Japanese children 17 .…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…In our study, although an interaction effect of baseline BMI and BMI changes on changes in academic performance over 2 years was noted, changes in BMI had no main effect on changes in academic performance over 2 years. These results could partly explain the weak or null association of BMI changes with academic performance in Asian children as previously reported 6,24 . Furthermore, a previous crosssectional study demonstrated an inverted U-shape relationship between BMI and academic performance in Japanese children 17 .…”
Section: Discussionmentioning
confidence: 47%
“…To the best of our knowledge, this study is the first to demonstrate that weight loss in children with overweight/ obesity and weight gain in children with underweight are associated with improvement in academic performance in Asian children. Recent longitudinal observational studies that targeted Asian children demonstrated a weak or null relationship between BMI and academic performance 6,24 . In our study, although an interaction effect of baseline BMI and BMI changes on changes in academic performance over 2 years was noted, changes in BMI had no main effect on changes in academic performance over 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We specifically examined if improvements in cardiorespiratory fitness had differential effects on an individual’s worst and best GPs. We focused on cardiorespiratory fitness, which several studies have indicated was positively associated with academic performance 3 – 5 , 7 , 10 , 11 , although the exact changes in fitness components that most contribute to improving academic performance remain unclear. Moreover, we rigorously controlled for potentially significant confounding variables, including out-of-school learning time and SES, when examining the association between cardiorespiratory fitness and academic performance.…”
Section: Introductionmentioning
confidence: 99%